Novel mitochondrial haplotype of spotted-tailed quoll (Dasyurus maculatus) present on Kangaroo Island (South Australia) prior to extirpation - Grealy, A.; McDowell, M.; Retallick, C.; Bunce, Michael; Peacock, D. (SAGE PUBLICATIONS LTD, 2020)
Spotted-tailed quolls (Dasyurus maculatus) – cat-sized, carnivorous marsupials – occupied Kangaroo Island (KI), South Australia, for over 50,000 years but became locally extinct following European settlement of the island in 1836. As the largest mammalian predator on KI when the Europeans colonised it, spotted-tailed quolls would have played a significant role in maintaining healthy ecosystem function. The reintroduction of spotted-tailed quolls to KI could redress some of these ecological benefits and would establish a refuge population of the species, which is considered endangered by the Australian government. However, before a reintroduction could be considered, the genetic relationship between KI’s spotted-tailed quolls and the currently recognised extant subspecies needs to be established. While subspecies are difficult to differentiate by skeletal morphology, they are genetically distinct. Here, we extracted ancient DNA from five left dentaries excavated from Kelly Hill Cave (KI) that were morphologically identified as D. maculatus. Following genetic confirmation of these identifications, we sequenced a 450-bp region of the mitochondrial D-loop to determine the subspecific genetic affiliation(s) of KI’s D. maculatus, and therefore the subspecies that may be the most appropriate candidate for reintroduction. We find that all five specimens are most closely related to the Tasmanian subspecies, but form a distinct monophyletic clade that may represent a new subspecies. Further research (including genotyping spotted-tailed quoll specimens from mainland South Australia and Western Victoria) is required before decisions are made regarding the sourcing of individuals for reintroduction to KI.